Shop Until You Drop: the Unexpected Effects of Anticonsumerism and Environmentalism - Giovanni Maccarrone; Marco A. Marini; Ornella Tarola (Fondazione Eni Enrico Mattei (FEEM), 2023)
In an economy where consumers are heterogeneous in their preferences over the hedonic and environmental attributes of goods on sale, we explore the effects of anti-consumerism and environmentalism. We show that when the environmental attributes of products come at the expense of the hedonic attributes, a higher supply of anti-consumerism and environmentalism yields the expected positive effect on the environment. In contrast, when hedonic and environmental attributes are jointly met by a good, higher levels of anti-consumerism and environmentalism negatively affect the society's environmental footprint. Moreover, the impact of anti-consumerism and environmentalism on social welfare is far from being obvious, giving rise to unexpected redistributive effects between firms and consumers.
Keywords: D11; L13; Q50; 330; environmentalism; hedonism; anti-consumerism; hedonic and environmental product attributes; vertical product differentiation